Amino acid digestibility and energy content of corn distillers meal for swine - Jacela, J.Y.; Sulabo, R.C.; Thaler, R.C.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (My University, 2009)
An experiment was conducted to determine the apparent ileal digestibility and standardized ileal digestibility of amino acids and energy of corn distillers meal in pigs. Five growing barrows (initially 150 lb) were allotted to one of two diets in a crossover design. One diet contained corn distillers meal (66.7%) as the sole protein source. The second diet was nitrogen-free to determine basal endogenous AA losses. Ileal digesta and fecal samples were collected during each period and analyzed for amino acid and energy contents. Based on these analyses, apparent ileal digestibility (AID), standardized ileal digestibility (SID), gross energy (GE), digestible energy (DE), metabolizable energy (ME), and net energy (NE) were calculated. Apparent ileal digestibility values of lysine, methionine, and threonine in corn distillers meal were 47.2, 79.4, and 64.1%, respectively while SID values of the same amino acids were 50.4, 80.4, and 66.3%, respectively. The ME, DE, and estimated NE values of the corn distillers meal were 1,137; 1,233; and 813 kcal/lb, respectively.
Keywords: Corn distillers meal; Feed ingredients; Digestibility; Swine